2022
DOI: 10.1227/neu.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Frailty With Vestibular Schwannoma Resection Outcomes and Machine Learning Development of a Vestibular Schwannoma Risk Stratification Score

Abstract: BACKGROUND: Patient frailty is predictive of higher neurosurgical morbidity and mortality. However, existing frailty measures are hindered by lack of specificity to neurosurgery. OBJECTIVE: To analyze the association between 3 risk stratification scores and outcomes for nationwide vestibular schwannoma (VS) resection admissions and develop a custom VS risk stratification score. METHODS: We identified all VS resection admissions in the National Inpatient Sample (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We read with great interest the recent publication by Tang et al 1 in neurosurgery examining frailty's association with postoperative morbidity and mortality after vestibular schwannoma (VS) resection. We anticipated further frailty and VS discussion after our 2021 publication in JAMA OTO-H&N, 2 which delineated how increasing frailty, and not increasing patient age, was an independent risk factor for postoperative morbidity and mortality, also using the National (Nationwide) Inpatient Sample (NIS).…”
mentioning
confidence: 99%
“…We read with great interest the recent publication by Tang et al 1 in neurosurgery examining frailty's association with postoperative morbidity and mortality after vestibular schwannoma (VS) resection. We anticipated further frailty and VS discussion after our 2021 publication in JAMA OTO-H&N, 2 which delineated how increasing frailty, and not increasing patient age, was an independent risk factor for postoperative morbidity and mortality, also using the National (Nationwide) Inpatient Sample (NIS).…”
mentioning
confidence: 99%
“…It is becoming increasingly clear that biological aging (vs. chronological aging) contributes to the development of chronic diseases and physical frailty at the molecular and cellular level which can lead to decline and death (Fougere et al, 2017 ). Furthermore, a cross-sectional study has shown that frailty is independently associated with mortality and prolonged hospital stays following vestibular schwannoma resection (Dicpinigaitis et al, 2021 ; Tang et al, 2022 ). Compared with advanced patient age alone, frailty may be more accurate for predicting vestibular schwannoma resection outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Myriad NIS studies across the neurosurgical literature have used these CCS-derived panels to identify perioperative complications. 2,9,10 The authors specifically raise concern for using the "S" identifier among ICD-10 codes to identify operative facial nerve injury. However, the ICD-10 "S" identifier is a direct counterpart to the 800-999 range of codes within the ICD-9 system denoting injury and poisoning.…”
mentioning
confidence: 99%
“…We appreciate the insightful letter submitted by Bowers et al 1 in response to our recent article, which used the Nationwide Inpatient Sample to create a custom risk stratification score for vestibular schwannoma (VS) resection outcomes (VS-5). 2 We commend their previous work in establishing how frailty predicts morbidity after VS resection. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation